The Effect of Digital Financial Literacy on Transaction Decisions on Tiktok Shop Among the People of Cirebon with Consumer Trust as a Mediating Variable - Vivi Aprilia Maharani; Ario Purdianto (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the effect of digital financial literacy on transaction decisions on TikTok Shop among the people of Cirebon, with consumer trust serving as a mediating variable. Data were collected through an online questionnaire distributed to 150 respondents in Cirebon who had conducted transactions on TikTok Shop at least once within the last three months. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that digital financial literacy has a positive and significant effect on transaction decisions (β = 0.368, p < 0.05) and consumer trust (β = 0.742, p < 0.05). Consumer trust also has a positive effect on transaction decisions (β = 0.501, p < 0.05) and acts as a full mediator in the relationship between digital financial literacy and transaction decisions (β = 0.372, p < 0.05). Furthermore, the research model explains 66.0% of the variance in transaction decisions (R² = 0.660). These findings indicate that improving digital financial literacy not only directly encourages transaction decisions but also indirectly through the development of consumer trust toward the TikTok Shop platform.